Beyond the Code- Why Emergency Departments in Pakistan Need Education in Leadership - Saima Ali; Syed Ghazanfar Saleem (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College)
Emergency medicine (EM) in Pakistan is evolving within an environment of escalating patient volumes, resource limitation, and increasing complexity of care. While clinical expertise continues to improve through expanded postgraduate training and global exposure, the critical component of EM leadership development is still under explored. EM leadership is central to delivering timely, safe, and efficient care in a high-stakes environment. Despite this, structured leadership programs specific to emergency departments (EDs) are almost non-existent across the country.